PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV INDAH BARU GROUP GENTENG - Oktadilah, Sofia; Syarifuddin, Syarifuddin (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2021)
This research is motivated by the results of primary data which states that the motivation and work environment of employees at CV Indah Baru is less than optimal. Companies want increased performance every year in order to be successful in facing competition, therefore employee performance is a concern because it will affect company performance. In order to improve employee performance, high motivation from employees and a good work environment are needed. The purpose of this study was to determine the effect of motivation and work environment on employee performance at CV Indah Baru Group. This research applies descriptive quantitative method. The population in this study were all permanent employees of CV Indah Baru Group which consisted of 73 people using saturated sampling. The data analysis used is descriptive analysis, classical assumption test and multiple regression analysis. Base on the results of descriptive analysis, motivation is included in the good category and also for the work environment it is in the good category while for the same employee performance it is in the good category. Based on the results of the study, it shows that motivation and work environment partially and simultaneously influence employee performance.